Партнерство та зростання: іт-менторство як ключовий елемент спільного успіху - Міхнов, Є. Д. (ХНУРЕ, 2024)
In the modern world of IT technologies, which are actively and dynamically developing, the role of mentoring remains extremely important. In heterogeneous IT environments, where employees of different specializations, genders, and personalities work together and perform a variety of activities, mentoring can be a key element of successful development. Mentors can provide valuable experience and knowledge that help new employees navigate a wide range of technology decisions and onboarding to a new team
Keywords: партнерство; спільний успіху